2022
DOI: 10.3389/fcvm.2022.907175
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Cardiac Clinical Needs in Adult Mucopolysaccharidoses

Abstract: The Mucopolysaccharidoses (MPSs) are a group of heterogenous disorders with complex multisystemic presentations. Although Haematopoietic Cell Transplantation (HCT) and Enzyme Replacement Therapy (ERT) have extended the lifespan of individuals affected with MPS well into adulthood, reversal of pre-existing cardiac, skeletal and neurocognitive deficits does not occur, so there are no truly curative treatments available to these patients at present. The medical and surgical management of cardiovascular problems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In the Phase 2 study, improvement in CIMT was observed in patients treated with odiparcil [ 24 ]. CIMT is correlated with carotid pathology and has been used as a marker predictive of cerebrovascular accidents in other chronic conditions including diabetes mellitus and hypertension [ [32] , [32] , [33] , [34] ]. CIMT measured using non-invasive carotid artery ultrasonography could be a feasible in vivo marker reflecting GAG accumulation and intimal medial proliferation in MPS VI patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the Phase 2 study, improvement in CIMT was observed in patients treated with odiparcil [ 24 ]. CIMT is correlated with carotid pathology and has been used as a marker predictive of cerebrovascular accidents in other chronic conditions including diabetes mellitus and hypertension [ [32] , [32] , [33] , [34] ]. CIMT measured using non-invasive carotid artery ultrasonography could be a feasible in vivo marker reflecting GAG accumulation and intimal medial proliferation in MPS VI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in treatments such as Haemopoietic Stem Cell transplantation (HSCT) and Enzyme Replacement Therapy (ERT), alongside increasing awareness amongst health care professionals has improved the life expectancy of this patient group [ 5 ]. HSCT and ERT have been shown to reduce progression of left ventricular hypertrophy [ 6 , 7 ] but neither influence valvular disease progression, in particular in MPS type I, II and VI [ 8 , 9 , 10 , 11 , 12 ], which remains an unmet need [ 13 ]. One study from Japan [ 12 ] has shown HSCT to improve and stabilise valvular pathology in children with MPS II.…”
Section: Introductionmentioning
confidence: 99%